Theoretical Investigation on Biological Activity of Imidazole Derivatives [Carbenzim, Mebendazole] by using (DFT) and (PM3) Methods - Tuma Musa, Amar; Abaid, Khalida (Al-Nahrain Journal of Science, 2021)
The theoretical study represents an essential preliminary stage for the start of any industry, as it gives a theoretical description of the properties of compounds (chemical, physical and biological properties) without conducting research to find out about this and the least cost. Through the theoretical study, we extract a clear picture of the chemical compounds before starting to manufacture them to know the extent of their impact on human health and their chemical and biological effectiveness. Using the Density Functional Theory (DFT/B3LYP) with base 6-311G, through Gaussian 09 program, the optimize geometry, (bond lengths, angles bond) and vibrational spectra was calculated of the benzimidazole derivatives [Carbenzim (CZM), Mebendazole (MBZ)].Through orbital charts of HOMO and LUMO to study electronic properties. The HOMO-LUMO gap was also evaluated for chemical reactivity and determination of global reactivity descriptors (Hardness (h), Softness (S), Electrophilicity (w), Chemicalpotential (m), Electronegativity(χ))] that defines compunds effectiveness and the their biological activities.In addition, (QSAR) data has been used to develop relationships between biological activities and thermophysical properties of chemicals, through the Hyper Chem 8.0 program by using Semi-empirical (SE) method at the (PM3) level. The LOG P value was calculated, binding energy, Polarizability, hydration energy, surface area, and electrostatic potential energy difference of two level.